PENDOKUMENTASIAN KEPERAWATAN PASIEN STROKE BERHUBUNGAN DENGAN PELAKSANAAN DISCHARGE PLANNING - Isna Ovari (LPPM UNIVERSITAS PERINTIS INDONESIA, 2017)
Discharge planning is one indicator of the quality of nursing care. Discharge planning will produce integrated relationship between the care received while in hospital with care after discharge, especially nursing actions performed correctly. The purpose of this study was to determine the relationship of stroke patient discharge planning with the nursing documentation in inpatient Hospitals Nationwide Stroke Bukittinggi 2015. This research is descriptive analytic with cross sectional approach. The population is all a team leader and primary nurse in the room neurology, IRNA B, and C IRNA floors 1 and 2. A sample of 35 people by using total sampling.The collection of data through observation and documentation that was done at 1-21 Februari 2015. Data processing by computer in the form of chi-square test. Results obtained over the majority of respondents (57.1%) do a complete discharge planning in stroke patients. More than the majority of respondents (60.0%) documented the discharge planning in stroke patients with complete. The test results obtained statistical significant relationship between the implementation of discharge planning stroke patients with nursing dokumentation with a value of p = 0.036. Conclusions from the study are expected from the hospital management can provide guidance and supervision on the implementation and documentation of discharge planning, so as a team leader and primary nurse can improve discharge planning and documentation of implementation.